PRESENCE AND ABSENCE OF QUANTITATIVE TRAITS LOCI (QTL) REGION ON CHROMOSOME Z AND ITS EFFECT ON SOME PRODUCTIVE AND PHYSIOLOGICAL TRAITS IN LOCAL IRAQI CHICKEN - B, G.M. Al-Khatib,; D. M. Zamil,; W. J. Al-Izzi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was carried out to identify the effect of the quantitative trait loci (QTL) region on some productive and physiological traits of Iraqi chickens. One hundred five and ten-week-old laying hens were used and bred in individual sages from sexual maturity to 100 days of production. Blood samples were collected from the brachial vein for DNA extraction and serum isolation, and then polymerase chain reaction (PCR) was done to determine the target region of the QTL. Two groups were obtained: the first had a PCR product with band 294 bp denoted (P) and the second had no PCR product denoted (NP). The P group had a significant (p < 0.05) effect on egg weight at the second stage of the study amounted 48.23 gm. and a significant (p < 0.05) effect was observed in egg shell weight amounted 6.97 gm. No significant effects were found in all productive, physiological, or qualitative traits.In conclusion, the presence and absence of QTL regions significantly affect egg weight and egg shell weight, which is suitable for selection programs to improve the genetic makeup of Iraqi chicken.